Some psychological problems of vocational guidance of early adolescents - Butayarov Bakhtiyor Isakovich (Zien Journals, 2022)
The article explains that career guidance is not only a social but also a psychological problem, that these two perspectives are always complementary, as well as the possibilities of individual psychological characteristics of career guidance.
Keywords: career orientation; social environment; psychological impact; the nature of; activity